The Taxation of Multinationals: Firm Level Evidence for Belgium - Hylke Vandenbussche; Chang Tan (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
This paper provides empirical evidence of a more favorable tax treatment for foreign multinationals compared to similar domestic firms in a small open economy. Using treatment effects to control for self-selection of foreign firms into low tax firms, we find that foreign multinationals have substantially lower effective tax rates compared to domestic firms. In our estimations we also control for firm size, sector membership and business-cycle effects. A simple theoretical framework is used to explain our empirical findings and rests on the notion that multinational firms are in a better position to bargain for lower taxes with governments as a result of their "footloose" nature and outside location options.
Keywords: C51; E62; F23; 330; firm level data; multinationals; corporate taxation; self-selection; Unternehmensbesteuerung; Multinationales Unternehmen; Belgien